Nonlinear finite element analysis (NLFEA) of reinforced concrete flat slabs with holes. (October 2020) - Marques, Marília G.; Liberati, Elyson A.P.; Pimentel, Mário J.; de Souza, Rafael A.; Trautwein, Leandro M.
Abstract: Nonlinear Finite Element Analysis (NLFEA) was used to simulate reinforced concrete flat slabs with shear reinforcement and holes. Fifteen slabs were subject to laboratory testing and then simulated on Diana software. Six slabs had shear reinforcement, and five slabs presented holes and shear reinforcement. Stud shear reinforcement was used in the study, with variation in the number of holes (two or four) and their size (75 mm, 100 mm and 150 mm). Numerical results of the finite element nonlinear analysis confirmed the accuracy of the proposed model, since they were in agreement with the experimental results in terms of final load, displacement and, for some slabs, failure mode. In addition, numerical and experimental results were compared with the recommendations of codes. The numerical results evidenced that holes affected punching shear strength, making it lower, while using studs increased the strength. The prediction accuracy of the failure loads presented by the numerical method was better than the results predicted by some selected codes.